The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.3922/j.psns.2014.032
|View full text |Cite
|
Sign up to set email alerts
|

Angular scale expansion theory and the misperception of egocentric distance in locomotor space.

Abstract: Perception is crucial for the control of action, but perception need not be scaled accurately to produce accurate actions. This paper reviews evidence for an elegant new theory of locomotor space perception that is based on the dense coding of angular declination so that action control may be guided by richer feedback. The theory accounts for why so much direct-estimation data suggests that egocentric distance is underestimated despite the fact that action measures have been interpreted as indicating accurate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
29
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 48 publications
(104 reference statements)
1
29
0
Order By: Relevance
“…Whereas it is frequently supposed that accurate actions depend on accurate perceptions, adaptation to prism goggles shows that, even when perception remains inaccurate, action can simply adapt (Harris, 1963). People who estimate that a target at 10 m is only 7 m away may nonetheless walk 10 m (accurately) to that target with their eyes closed (Loomis, Da Silva, Fujita & Fukusima, 1992) but perceive themselves to have walked only 7 m because perceived walked distance is calibrated to their visual experience (Durgin, 2014; Durgin, Fox & Kim, 2003; Durgin et al, 2005; Riemer, Hölzl & Kleinböhl, 2014). Similarly, hills also feel extremely steep underfoot (Hajnal, Abdul-Malak & Durgin, 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas it is frequently supposed that accurate actions depend on accurate perceptions, adaptation to prism goggles shows that, even when perception remains inaccurate, action can simply adapt (Harris, 1963). People who estimate that a target at 10 m is only 7 m away may nonetheless walk 10 m (accurately) to that target with their eyes closed (Loomis, Da Silva, Fujita & Fukusima, 1992) but perceive themselves to have walked only 7 m because perceived walked distance is calibrated to their visual experience (Durgin, 2014; Durgin, Fox & Kim, 2003; Durgin et al, 2005; Riemer, Hölzl & Kleinböhl, 2014). Similarly, hills also feel extremely steep underfoot (Hajnal, Abdul-Malak & Durgin, 2011).…”
mentioning
confidence: 99%
“…For example, directional visual variables used to control locomotor action might be densely coded in order to provide greater effective perceptual sensitivity for control (Durgin, 2014; Hajnal et al, 2011; Li & Durgin, 2009). Given that the sensitive control of action is normally tantamount for survival, this theory of dense angular coding provides an account of why systematic bias in the perception of space might be selected for by evolutionary processes.…”
mentioning
confidence: 99%
“…One of the goals of the present work was to test how well these data fit a recently proposed model that has been shown to fit outdoor hills and indoor surfaces alike (Durgin, 2014;, 2012. Durgin and Li (2012) showed that perceived slant exaggerates actual slant by a factor of about 1.5 for a range of angles up to 60°.…”
Section: Discussionmentioning
confidence: 99%
“…Information in perspective assists the perception of 3-D scenes (Banks, Cooper, & Piazza, 2014;Bruggeman, Yonas, & Konczak, 2007;Durgin, 2014;Hammad, 2015;Juricevic & Kennedy, 2006;Sedgwick, 1986;Todorović, 2005;White, 1956;Williams & Durgin, 2015). However, for centuries scholars have argued about how (from Alhazen, 1039/1989, and Berkeley, 1709/1975, to moderns such as Kubovy, 1986;Yang & Purves, 2003;and Kennedy & Wnuczko, 2015).…”
mentioning
confidence: 99%
“…We focus here on the perception of scene angles, and our suggestion is that foreshortening leads to major errors. Durgin (2014) noted that z distances are often underestimated visually. For a standing observer, distances from the vantage point, such as 20 m along a z-line, may be estimated as about 14 m; that is, Bnear-walking^z distances are underestimated visually by about 30 %.…”
mentioning
confidence: 99%